Protecting the rights and freedoms in the aspect of human trafficking - Скулиш, Євген Деонізійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article is devoted to the problem of human trafficing in the aspect of human rights and freedoms protection.For effective protection of human rights not only national legislation improvement according to the international standards but the mechanisms of its execution is needed.